The Influence of Work Discipline and Compensation on Employee Performance at PT. Multiarindo Surabaya - Ramadhan, Dicky; Irbayuni, Sulastri (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
In the current era of globalization, many significant changes have occurred in life in various sectors, especially in the industrialization sector. One of the main challenges in the industrialization sector is in the field of personnel, where the challenge is in terms of managing organizational resources effectively and eliminating ineffective practices, management is required to always develop new ways to attract and retain high-calibre employees and managers. the level required for an organization to be able to compete. This research aims to research and analyze the influence of work discipline and compensation on employee performance at PT Multiarindo Surabaya. The sample in this study was 60 respondents using a saturated sample with Likert scale weighting. The data analysis technique uses the Structural Equation Model- Partial Least Square (SEM-PLS). The research results showed that Work Discipline had a positive and significant effect on employee performance. Compensation has a positive and significant effect on the performance of PT Multiarindo Surabaya employees.